Analisis Manajemen Keuangan pada Usaha Peternakan Kemitraan Ayam Broiler Skala Rakyat - Sukarno, Taufan Daniarta (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
Poultry sectors contributed 2,51% of GDRP in the Central Java Province, where Semarangcontributed 1.135.487 kg of Broilers chicken in 2016. Plasma-core partnership is one of the most used business cooperation types amongst the poultry farmers. Classification in poultry business scale divides into 3 classes, which were: Small Scale (â‰¤5.000 heads), Medium Scale (5.001-10.000 heads) and Large Scale (>10.000 head). The purpose of this study is to estimate the operating cashflows and revenue. The benefit of this study is to detect the profits and anticipate losses in poultry farming. This study used Survey methods, location arrangement used purposive sampling and data collected by interviews with the owners. Data analysis used revenue and operating cash flow computation. The results of this study show the net revenue of this poultry farm is IDR.171.488.834, while the operating cash flows are IDR.170.286.117,65. The cost of chicken seedlings purchase and its feed is the most expensive amongst all subjects. Clustering results shows that this poultry was categorized as Small scale poultry, where itâ€™s population is only 4.000 chickens, but are profitable and worthy to expand, and makes it one of the most longest-living poultry farms in the region